Imaginative Minds - Roth, Ilona (Oxford Oxford University Press, 2007)
Imagination is one of the most distinctive characteristics of human thought. The supreme powers of flexibility, supposition and inventiveness that are its hallmarks, whether in science, technology, business or the visual, literary and performing arts, are highly prized in contemporary societies. Yet in the fields of psychology and cognitive science, where we might expect to find the topic 'centre-stage', there has been comparatively little work. This volumes addresses this omission by bringing together the theories and methods of these disciplines with other perspectives offering important insights into the imagination. The 15 chapters address key questions about the imaginative workings of the mind, including how the capacity for imagination evolved, how it is expressed and what roles it plays in children's thinking, what psychological processes and brain mechanisms are involved, and how imagination operates in universal cultural phenomena such as music, fiction and religion, which are both the fruits of and the 'fuel' for imaginative minds. The exceptional interdisciplinary scope of the volume, and its exploration and juxtaposition of different forms of imaginative cognition, offer an engaging and innovative take on the topic, bringing together approaches from psychology, cognitive science, anthropology and evolutionary studies with philosophy and the humanities. Distinguished contributors demonstrate their own imaginative flair in a fascinating and varied collection of essays about this most elusive and special human capacity.
Keywords: Philosophy; Imagination